The novel inositol lipid phosphatidylinositol 3,4-bisphosphate is produced by human blood platelets upon thrombin stimulation. - Sultan, C (1990)
Radioactive PtdIns(3)P was detected in human platelets incubated with [32P]Pi, but remained unaffected by thrombin treatment. In contrast, [32P]PtdIns(3,4)P2 was absent from resting platelets, but was produced by thrombin-activated platelets in a dose- and time-dependent manner. [32P]PtdInsP3 was never found under these conditions. These changes are similar to those elicited in other cells by platelet-derived growth factor or the oncogene product pp60c-src.